2015
DOI: 10.1590/s0102-67202015000100019
|View full text |Cite
|
Sign up to set email alerts
|

Early surgical complications after gastric by-pass: a literature review

Abstract: IntroductionGastric bypass is today the most frequently performed bariatric procedure,but, despite of it, several complications can occur with varied morbimortality. Probably all bariatric surgeons know these complications, but, as bariatric surgery continues to spread, general surgeon must be familiarized to it and its management. Gastric bypass complications can be divided into two groups: early and late complications, taking into account the two weeks period after the surgery. This paper will focus the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
19

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(62 citation statements)
references
References 34 publications
(56 reference statements)
2
33
0
19
Order By: Relevance
“…Much less frequently, the bleedings are caused by iatrogenic injuries of the liver and spleen or trocar wounds. The majority of late postoperative bleedings are intraluminal [5,7]. They may develop several months and even years after surgery, being most commonly caused by ulcers in gastrojejunoanastomosis or the remnant stomach and duodenum [1,4,6,7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much less frequently, the bleedings are caused by iatrogenic injuries of the liver and spleen or trocar wounds. The majority of late postoperative bleedings are intraluminal [5,7]. They may develop several months and even years after surgery, being most commonly caused by ulcers in gastrojejunoanastomosis or the remnant stomach and duodenum [1,4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…The bleeding which starts 6 hours postoperatively and is accompanied by hematocrit rate reduction is usually the evidence of continuous bleeding, in most cases requiring urgent surgical intervention. On the contrary, if gastrointestinal bleeding occurs 48 hours after surgery and hematocrit rate is not significantly changed there is no need for active surgical manipulations [3,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal insufflation is performed at 14 mmHg was obtained with a Veress needle placed through the umbilicus of the patient (27,(33)(34)(35)(36)(37). Trocar placement: 10 mm in the midline (between xyphoid and umbilicus); two of 12 mm, one in the right upper quadrant and a left one in the mid-clavicular line; after that two more 5-mm trocars were used, one for liver retraction just distal to the xyphoid; and the other 5-mm of distal to the costal margin ( Figure 1A,B).…”
Section: Rygb Technique Descriptionmentioning
confidence: 99%
“…Several trials demonstrated that the duodenum and jejunum sense nutrients and initiate a feedback response through the gut-brain-liver axis to regulate hepatic glucose production. When nutrients are delivered to medium jejunum led a greater insulin sensitivity for glucose and fatty acids (20,26,(31)(32)(33)(34)(35)(36)(37)(38)(39). …”
mentioning
confidence: 99%